Stalin’s agricultural collectivization activities in Kazakhstan (ХX C. 20-30) - G. M., Karasayev; S. T., Nabiyev; K. A., Yensenov; B. S, Zhumagulov; A. A., Oskembay (Opción, 2020)
This scientific article describes the goals, processes and consequences of destroying the rich and middle-class people in the Kazakh Soviet Union, including the Stalinist totalitarian authority in the 20s and 30s of the twentieth century, as well as the destruction of the rich and the middle-class in Kazakh agriculture. The villagers, completely withdrawn from their livestock and forced into collective farms, joined the armed uprising in all parts of Kazakhstan. However, such uprisings were severely suppressed. These statements are made on the basis of specific archives and historical sources, and scientific conclusions have been made.